Electric energy cooperation in the Baltic Sea region and the role of Russia in it - Zverev Yuri (Baltic Region, 2013)
This article examines cooperation in the electric energy sector in the Baltic region. The author explores the existing undersea HVDC power exchange projects. It is emphasised that cooperation in the electric energy sector is concentrated largely in the EU member states despite earlier plans to establish the Baltic energy ring, which would also include Russia and Belarus. The author stresses that one of the most acute problems for the EU today is overcoming isolation of the energy systems of the Baltic States (Lithuania, Latvia, and Estonia) from that of the major part of the EU. This task has become especially relevant after the closing of the Ignalina NPP (Lithuania), which used to be the primary energy source for the three Baltic States. The article examines key projects of the construction of new international power transmission lines in the framework of the Baltic Energy Market Interconnection Plan (BEMIP) and the prospects of the Visaginas NPP (Lithuania) in solving energy problems of the Baltic States. The author analyses Russia’s role in the electric energy market and focuses on a possible increase of the country’s energy market share following the construction of the Baltic NPP and the export of generated electric energy to Poland, Lithuania, Germany, and Sweden. The author concludes that the prospects of Russia’s energy export to the Baltic Sea region will be determined not only by technological, economic and market factors, but rather by the general state of relations between Russia and the EU. Moreover, a lot depends on Lithuania’s decision on the construction of the Visaginas NPP, as well as the way the EU and the Baltic States solve the problem of energy supply in case the NPP project is terminated.